Partisipasi Masyarakat dalam Pengelolaan Taman Desa: Studi di Desa Sibuak, Kabupaten Kampar - Ayub, Daeng; Raja, Faisal Hamid Maka; Handoko, Tri; Jais, M. (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Abstract: This study aims to analyze community participation in the management of the village park in Sibuak Village, Tapung District, Kampar Regency, focusing on forms of participation, influencing factors, the role of the village government, and management challenges. This qualitative case study was conducted over six months in 2026. Fourteen informants were selected purposively, consisting of the village head, three village officials, two park managers, two community leaders, and six residents or park users. Data were collected through observation, semi-structured in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Data credibility was strengthened through source, technique, and time triangulation. The findings show that community participation occurs through gotong royong, park maintenance, use of the park as a social and recreational space, and involvement in village activities. However, participation is not evenly distributed. It is more visible at the implementation and utilization stages, while involvement in planning, decision-making, and evaluation remains limited. Participation is influenced by community awareness, communication, village leadership, time availability, and perceived benefits. The village government acts as a facilitator, motivator, and coordinator, but management remains constrained by limited community awareness, budget, coordination, and the absence of a sustainable management mechanism. The novelty of this study lies in mapping community participation across four stages and relating these stages to collaborative conditions in village park management. The findings are context-specific to one village and should not be generalized without considering differences in local social and institutional conditions. Abstrak: Penelitian ini bertujuan menganalisis partisipasi masyarakat dalam pengelolaan Taman Desa di Desa Sibuak, Kecamatan Tapung, Kabupaten Kampar, dengan fokus pada bentuk partisipasi, faktor yang memengaruhi partisipasi, peran pemerintah desa, dan kendala pengelolaan. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus dan dilaksanakan selama enam bulan pada tahun 2026. Sebanyak 14 informan dipilih secara purposive, terdiri atas kepala desa, tiga perangkat desa, dua pengelola taman, dua tokoh masyarakat, dan enam masyarakat atau pengguna taman. Data dikumpulkan melalui observasi, wawancara mendalam semi-terstruktur, dan dokumentasi, kemudian dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña. Keabsahan data diperkuat melalui triangulasi sumber, teknik, dan waktu. Hasil penelitian menunjukkan bahwa partisipasi masyarakat diwujudkan melalui gotong royong, pemeliharaan taman, pemanfaatan taman sebagai ruang sosial dan rekreasi, serta keterlibatan dalam kegiatan desa. Namun, partisipasi belum merata; keterlibatan lebih tampak pada tahap pelaksanaan dan pemanfaatan, sedangkan keterlibatan dalam perencanaan, pengambilan keputusan, dan evaluasi masih terbatas. Partisipasi dipengaruhi oleh kesadaran masyarakat, komunikasi, kepemimpinan pemerintah desa, ketersediaan waktu, dan manfaat yang dirasakan. Pemerintah desa berperan sebagai fasilitator, motivator, dan koordinator, tetapi pengelolaan masih menghadapi keterbatasan kesadaran, anggaran, koordinasi, dan mekanisme pengelolaan berkelanjutan. Kebaruan penelitian ini terletak pada pemetaan partisipasi dalam empat tahap dan keterkaitannya dengan kondisi kolaboratif dalam pengelolaan taman desa. Temuan terbatas pada konteks satu desa sehingga penerapannya pada desa lain perlu mempertimbangkan kondisi sosial dan kelembagaan setempat.